Sosialisasi & Edukasi Pasar Modal Syariah Dalam Program Jariaah Bursa Efek Indonesia Di Pondok Pesantren Babussalam Mojoagung Jombang - Verlandes, Yuliasnita; Fitri Isnaini, Nurdiana; Hadi Purnomo, Agoes (Fakultas Ekonomi Universitas Islam Majapahit, 2023)
The Islamic capital market is one of the new breakthroughs in advancing the people's economy. The Sharia Capital Market is all activities in the capital market that do not conflict with the principles of Islamic teachings. The Indonesian Islamic capital market is part of the Islamic financial industry which is regulated by the Financial Services Authority (OJK) and synergizes with the Indonesian Stock Exchange as the capital market regulator in Indonesia. The background of this activity is to introduce the Jariaah program as one of the programs carried out by the Indonesia Stock Exchange to introduce the Islamic capital market among Islamic boarding schools and improve the performance of the Investment Gallery at the Indonesia Stock Exchange, Islamic University of Majapahit (GI BEI UNIM). After going through a direct visit, a very extraordinary welcome was obtained from the Pondok Pesantren and hoped that this activity could continue.